Transmission of 18 keV negative ions Cl- through nanocapillariesin Al2O3 membrane - 吕学阳 陈林 陈熙萌 贾娟娟 周鹏 周春林 邱玺玉 邵剑雄 崔莹 尹永智 王宏伟 姬明超 (Chinese physics B, 2011)
We investigate the angular distribution of the transmitted 18keV negative ions Cl- through Al2O3 nanocapillaries of 50 nm in diameter and 10 μm in length. Elastic scattering ions and inelastic scattering ions are obtained simultaneously. The experimental result is partially consistent with the guiding effect. We can qualitatively explain our experimental result through a dynamic process.